Education in the Times of Pop Culture. Pedagogy of Popular Culture in the Contemporary Educational Practice - Wierzba, Paulina (INSTED: Interdisciplinary Studies in Education & Society, 2015)
In the article I emphasize the need to use the pedagogy of popular culture in the contemporary educational practice. I refer to the experience of Western educators, such as Glen Savage, Ernest Morell, Craig Keller, Thomas Fain and Kate Sciurby who use in their work popular culture texts, seeing their educational potential. The author focuses on the entrance of the hip-hop culture to school and on the critical analysis of popular films and TV series. Wishing to reach today?s youth, for which popular culture is a fundamental element of cultural capital, it must not be forgotten that ignoring popular culture in the education process disdains today?s youth, and can cause problems in the work of teachers with students.